Inducing Human Motor Adaptation Without Explicit Error Feedback: A Motor Cost Approach - Xu, Yangmengfei; Crocher, Vincent; Fong, Justin; Tan, Ying; Oetomo, Denny (IEEE transactions on neural systems and rehabilitation engineering, 2021)
Recent studies have shown that motor adaptation is an optimisation process on both kinematic error and effort. This work aims to induce a motor adaption in an experimental setup solely relying on the effort without any explicit kinematic error. In this experiment, the intervention space and adaptation space are decoupled: while the force field only applies to the hand linear velocity, the adaptation is expected to happen in the arm joint null space ( i.e. the swivel angle). The primary hypothesis is that such an effort-based force field can induce a movement pattern change in an indirect manner. Secondarily, assuming that this adaptation may be further promoted through subtle prompts to explore the cost space, a variation of the approach with a progressive goal is also tested. Twenty naive subjects were allocated into two groups with slightly different implementations of the force field: one with a Constant Goal (CG) and another one with a Progressively changing Goal (PG). Subjects were asked to perform reaching tasks while attached to a 3D manipulandum. During the intervention, the device applied a resistive viscous force at the subject's hand as a function of the subject's swivel angle to encourage an increase of the latter. Significant increases of the swivel angle of 4.9° and 6.3° were observed for the CG and the PG groups respectively. This result confirms the feasibility of inducing motor adaptation in the redundant joint space by providing a task space intervention without explicit error feedback.